The Male Factor: Outcomes from a Cluster Randomized Field Experiment with a Couples-based HIV Prevention Intervention in a South African Township - Wechsberg, Wendee M. (Drug Alcohol Depend, 2016)
BACKGROUND: This study examined the effects of the Couples Health CoOp intervention on heavy drinking, condom use, and HIV incidence. METHODS: Thirty neighborhoods from one South African township were cluster randomized into three intervention arms: Couples Health CoOp (CHC), Women’s Health CoOp/Men’s Health CoOp (WHC/MHC), or a comparison arm. We recruited 290 men from informal drinking establishments who reported drinking alcohol regularly. We also recruited their main heterosexual sex partners. RESULTS: At 6-month follow-up, men in the CHC arm were less likely to report heavy drinking (OR 0.47, 95% CI: 0.25, 0.90) and were more likely to report consistent condom use during the past month (OR 2.66, 95% CI: 1.23, 5.76) than men in the comparison arm. At baseline, 26% of women and 13% of men were HIV-infected; at 6-month follow-up, 16 females and 5 males had seroconverted. HIV incidence was significantly lower among women in the CHC arm (IRR 0.22, 95% CI: 0.04, 1.01) than in the WHC/MHC arm. CONCLUSIONS: A couples-based intervention focusing on intersecting risks for HIV can improve biobehavioral outcomes, underscoring the importance of engaging couples together in HIV prevention.